Social relational factors of excessive internet use in four European countries - Mikuška, Jakub; Smahel, David; Dedkova, Lenka; Staksrud, Elisabeth; Mascheroni, Giovanna; Milosevic, Tijana (International journal of public health, 2020)
OBJECTIVES: Adolescents who deal with more emotional problems have been found to seek escape online, and struggle with excessive internet use (EIU). Poor social relationships have been linked with emotional problems. The current study investigated positive family and school relationships as protective factors against emotional problems and a preference for online social interaction (POSI), both specified as mediators of the association of family and school relationships with EIU. Cross-cultural differences in the model were tested. METHODS: A multi-group SEM was tested on representative samples of 4104 adolescents (Mage = 14.40 years, SD = 1.65, range 12-17, 50% female) from four European countries from Southern, Northern, Central, and Eastern Europe (Italy, Norway, Czech Republic, and Serbia, respectively). RESULTS: Results suggested consistent associations across countries. Positive family relationships and positive school relationships were associated with lower EIU, with 63-64% of the effect of family, and 91-93% of the effect of school relationships mediated by emotional problems and POSI. CONCLUSIONS: Positive family and school relationships protect adolescents against excessive internet usage, regardless of culture and indirectly-through emotional problems and POSI.
Keywords: Preference for online social interaction; IPARTheory; Humans; chování mladistvých; dítě; používání internetu; Child; Schools; interpersonální vztahy; Itálie; Female; Family Relations; Excessive internet use; lidé; Norway; Emotional problems; ženské pohlaví; sociální izolace; školy; Adolescent Behavior; Male; Adolescent; Czech Republic; Srbsko; Serbia; rodinné vztahy; Social Isolation; Internet Use; Česká republika; mužské pohlaví; Italy; Norsko; Interpersonal Relations; mladiství